A review of the use of lifting belts - Renfro, G. J.; Ebben, W. P. (Strength and Conditioning Journal, 2006)
Evidence shows that endothelial dysfunction precedes the development and progression of atherosclerosis. Recently, several studies have shown that exercise training can improve and potentially reverse endothelial dysfunction. This article presents basic information on endothelial function and the role of exercise in preventing and improving dysfunction. Part 1 of this column was published in Strength Cond. J. 27(5):31-33. 2005.